2000
DOI: 10.1210/jc.85.5.2034
|View full text |Cite
|
Sign up to set email alerts
|

Male-to-Female Transsexuals Have Female Neuron Numbers in a Limbic Nucleus

Abstract: Transsexuals experience themselves as being of the opposite sex, despite having the biological characteristics of one sex. A crucial question resulting from a previous brain study in male-to-female transsexuals was whether the reported difference according to gender identity in the central part of the bed nucleus of the stria terminalis (BSTc) was based on a neuronal difference in the BSTc itself or just a reflection of a difference in vasoactive intestinal polypeptide innervation from the amygdala, which was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
164
0
12

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(186 citation statements)
references
References 0 publications
10
164
0
12
Order By: Relevance
“…Postmortem studies have observed sex-atypical volumes and neuronal numbers in hypothalamic nuclei in the brains of individuals with GD (Garcia-Falgueras and Swaab, 2008;Kruijver et al, 2000;Zhou et al, 1995). Brain structure in individuals with GD has also been investigated in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Postmortem studies have observed sex-atypical volumes and neuronal numbers in hypothalamic nuclei in the brains of individuals with GD (Garcia-Falgueras and Swaab, 2008;Kruijver et al, 2000;Zhou et al, 1995). Brain structure in individuals with GD has also been investigated in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Clear anatomical sex differences have also been described in the human bed nucleus of the stria terminalis (BST). The darkly staining posteromedial component of the BST (BST-dspm) and the central subdivision of the BST (BSTc) are both larger in men than in women (Allen and Gorski, 1990;Zhou et al, 1995;Kruijver et al, 2000). Differences in the size of the human BSTc have been related to the gender identity disorder transsexuality, in which subjects voice the strong feeling of being born in the wrong sex.…”
mentioning
confidence: 99%
“…[18][19][20] This observation was refined, and it could further be shown that the one brain of a female-to-male transsexual available for post-mortem examination showed a male differentiation of the bed nucleus of the stria terminalis. 20 This finding of a biological index of female brain differentiation in male-to-female transsexuals could mark a conceptual turning point in the approach to transsexualism.…”
Section: Sexual Differentiation Of the Brainmentioning
confidence: 91%